Ambiguous Geographies: Connecting Case Study Knowledge with Global Change Science. Issue 3 (3rd May 2016) - Margulies, Jared D.; Magliocca, Nicholas R.; Schmill, Matthew D.; Ellis, Erle C.
Abstract : Case studies have long been a gold standard for investigating causal mechanisms in human–environment interactions. Yet it remains a challenge to generalize across case studies to produce knowledge at broader regional and global scales even as the effort to do so, mostly using metastudy methods, has accelerated. One major obstacle is that the geographic context of case study knowledge is often presented in a vague and incomplete form, making it difficult to reuse and link with the regional and global contexts within which it was produced and is therefore most relevant. Here we assess the degree to which the quality of geographic description in published land change case studies limits their effective reuse in spatially explicit global and regional syntheses based on 437 spatially bounded cases derived from 261 case studies used in published land change metastudies. Common ambiguities in published representations of case geographic contexts were identified and scored using three indicators of geographic data quality for reuse in spatially explicit regional and global metastudy research. Statistically significant differences in the quality of case geographic descriptions were evident among the six major disciplinary categories examined, with the earth and planetary sciences evidencing greater clarity and conformance scores than other disciplines. The quality of case geography reporting showed no statistically significant improvement over the past fifty years. By following a few simple and readily implemented guidelines, case geographic context reporting could be radically improved, enabling more effective case study reuse in regional to global synthesis research, thereby yielding substantial benefits to both case study and synthesis researchers.